AGRO-ECOLOGICAL EVALUATION OF TROPICAL FARMING SYSTEMS USING EMERGY: IN RIODE JANEIRO - BRAZIL - Albino, Juan Carlos Torrico; Callado, Sandra Maria Guimarã es (Emirates Journal of Food and Agriculture, 2017)
The article is based on an agro-ecological evaluation of seven different agricultural systems in Teresó polis, Rio de Janeiro. The studied systems are dealing with: vegetable production system, ecological husbandry, cattle production system, sylvopastoral approaches as well as citrus cropping systems. The main objective is to evaluate the environmental impact of these systems using the ?Emergy Analysis? as methodology. For this purpose, input data as materials, services, natural renewable/nonrenewable sources of 42 crops were analyzed. This method is based on energy flows, transforming all inputs and outputs in a common unit. This analysis allows comparisons across agricultural systems and their environmental impacts, as well as, makes possible the identification of scenarios to achieve greater sustainability. The main conclusions of this study are: the vegetable systems have large amounts of energy invested in irrigation, fertilizers and fuels; the largest value of sustainability corresponds to the ecological systems and it has the capacity to save capital in form of biomass in the system; cattle system causes bigger environmental damage and have the smallest yield per hectare in economic and energy terms; as for the citrus systems, a low investment rate was found and the use of renewable resources from this system is comparable to the vegetable systems.